Isolation and Phylogenetic Analysis of a Hunnivirus Strain in Water Buffaloes From China - Liu, Haifeng; Zhu, Xinyue; Dong, Qinting; Qiao, Chengpeng; Luo, Yuhang; Liu, Yi; Zou, Yanlin; Liu, Huanghao; Wu, Cuilan; Su, Jieyu; Peng, Hao; Ouyang, Kang; et al. (Frontiers in Veterinary Science, 2022)
In recent years, hunniviruses have been reported in a variety of animal species from many countries. Here, hunnivirus was detected in fecal samples from water buffaloes and named as BufHuV-GX-2106. The samples were inoculated into cultures of MDBK cells supplemented with TPCK trypsin and the BufHuV-GX-2106 strain was stably passaged and replicated. Electron microscopic analysis showed the BufHuV-GX-2106 virus particles were spherical and 20 30 nm in diameter. The complete genome of a plaque purified sample of BufHuV-GX-2106 was determined and analyzed. Genomic analysis revealed that the whole sequence of BufHuV-GX-2106 was 7,601 nucleotides (nt) in length and consisted of a large open reading frame of 6,759nt, a 5′UTR, a 3'UTR and a poly(A) tail. The complete genome sequence of BufHuV-GX-2106 shares 68-85% nucleotide identities with other known hunnivirus strains, indicating high genetic heterogeneity among these viruses. Phylogenetic analysis showed that BufHuV-GX-2106 belonged to the Hunnivirus A species and was more closely related to ovine hunnivirus than other known viruses of this type. This study describes the first isolation and complete genome sequence of a hunnivirus strain from water buffaloes. In addition, this study will help to understand the mechanisms involved in the pathogenesis of Hunnivirus A among different animal species.